Village Development Board its Role and Function in Supervision of Village Government in Bareng District, Jombang District East Java Province - Ruslie, Ahmad Sholikhin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The enactment of Law Number 6 of 2014 concerning Villages has had a significant influence, especially on the preparation of development funds and activities for villages from the government. So village heads and village officials are required to build a good system, from planning, implementation and supervision. The Village Consultative Body (BPD), which consists of several elements and village figures, is expected to be able to carry out its function as a carrier of community aspirations regarding the running of village government, monitoring development and empowering the community. This article is the result of a literature and empirical study of the role of BPD in Bareng District, Jombang Regency, in order to determine the role of BPD in carrying out its functions, along with the increasing transfer of funds from the central government to the regions which also influences the increase in funds received to villages. For this reason, BPD has a strategic position. As supervisor of the running of Village government including village development. The BPD and the Village Head must work together without having to argue. Therefore, this research focuses on how BPD carries out its role in supervising the running of government and village development, including the use of village finances. As well as the relationship between the BPD and the village head. Apart from that, it also explains what factors can support optimizing the role of BPD, including absorbing community aspirations. The synergy between the BPD and the Village Head as well as the BPD's ability to build aspirational communication with the community are important factors in the success of the BPD in carrying out its duties and functions